Py-GC/MS as a complementary technique for the chemical characterization of small microplastics (<100 μm) in polar samples - Gregoris, Elena (Zenodo, 2021)
Introduction Microplastics are a class of emerging pollutants of great concern, since they are widelydistributed in the environment and biota, and have also been found in polar regions(Iannilli et al., 2019). Currently there are no standard methods for the identification andquantification of microplastics in environmental samples. Micro-FTIR is a nondestructivespectroscopic technique, that allows polymer identification and quantificationin abundance and weight (Corami et al. 2020 and 2021); thanks to the instrument'simaging, particle morphology and size can be evaluated. Mass-based analytical methods– like pyrolysis gas chromatography-mass spectrometry (Pyr-GC/MS) - lack theinformation on particle size and morphology, but they are time efficient and permit asuccessful identification of polymer types and quantification of plastic weight (Müller etal., 2020). The cross-validation among techniques allows the standardization ofpretreatment and analytical methods. In this abstract, we describe the state of the art ofour work, whose aim is a cross-validation of two different techniques: quantification (i.e.,abundance and weight) and simultaneous identification of microplastic particles (MPs)and small MPs (SMPs) using Micro-FTIR, and identification and quantification of MPsand SMPs using Pyr-GC/MS. These techniques will be employed for the analysis of polarsamples. Activities The first phase of the work was dedicated to recognizing the characteristic pyrolysisproducts necessary to identify some standard polymers plastic materials. Preliminaryresults were obtained from different environmental matrices. Few water samples fromVenice Lagoon and few permafrost samples collected in Svalbard Islands were analyzedvia Micro-FTIR and Pyr/GC-MS. The identification of the single peaks in chromatogramswas carried out using the NIST 05 library and based on the information available in theliterature. The presence of PE was confirmed in all the samples with both techniques. Ourdata suggest that Pyr-GC/MS could be successfully used for ...